Evaluating Stellenbosch University students’ perceptions, knowledge and the factors affecting willingness-to-pay for organic vegetables - Mtwesi, Sinako (Stellenbosch : Stellenbosch University, 2024)
Thesis (MAgric) --Stellenbosch University, 2024.